Synergism Effect Between Inoculum Size and Aggregate Size on Flavonoid Production In Centella Asiatica (L.) Urban (Pegaga) Cell Suspension Cultures - Tan, Suat Hian; Maziah, Mahmood; Ariff, Arbakariya (eSAT Publishing House Pvt. Ltd., 2013)
The present study aimed to investigate the effect of different culture conditions on biomass content and flavonoid production of the elite C. asiatica accession UPM03. When 0.1 g inoculum 25 mL-1 of cell was grown in Murashige & Skoog (MS) medium supplemented with 2 mg 2,4-D l-1 and 1 mg kinetin l-1, flavonoids were not significantly produced in cells or released into the culture medium. Production of flavonoid was correlated with the aggregation size and inoculum density. At aggregate size of 250-500 μm with 0.3 g inoculum density 25 mL-1, it gave the highest luteolin content with 35.45 μg g-1 DW. After investigating the effect of culture conditions, i.e. pH, inoculum density, light irradiation and plant growth regulator, we found that with the optimized condition (i.e.250-500 μm aggregate size, 0.5 g wet cell 25 mL-1 supplemented with 3 mg L-1 2,4-D and 1 mg L-1 kinetin at pH 5.7 under 16hphotoperiod) the luteolin content was 11-fold higher than the cell suspension cultured at an inoculum size of 0.3 g wet cell 25 mL-1 with 250-500 μm aggregate size.